Distance Matters: Examining the Factors That Impact Prisoner Visitation in Minnesota - Clark, Valerie A. (Criminal justice and behavior, 2017)
One of the untested assumptions within the prison visitation literature is that inmates receive fewer visits when visitors must travel long distances to prisons. Measuring distance by comparing the addresses of the prisons where offenders were confined with the residential addresses of those who visited them, we tested this hypothesis by estimating the effects of distance on the number of times Minnesota prisoners were visited. We estimated the effects of distance by performing multilevel repeated measure analyses, measuring the frequency of visitation across the different facilities at which inmates were housed, the different neighborhoods from which they received visits, and between-inmate differences in visitation frequency. Besides distance, we also estimated the effects of social disorganization on the frequency of visitation. Finding that distance does indeed decrease the frequency of prison visitation, as does concentrated disadvantage in neighborhoods, we discuss the implications of this research for prison administrative policies.